2023
DOI: 10.3390/genes14010167
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Regions Associated with Wool, Growth and Reproduction Traits in Uruguayan Merino Sheep

Abstract: The aim of this study was to identify genomic regions and genes associated with the fiber diameter (FD), clean fleece weight (CFW), live weight (LW), body condition score (BCS), pregnancy rate (PR) and lambing potential (LP) of Uruguayan Merino sheep. Phenotypic records of approximately 2000 mixed-age ewes were obtained from a Merino nucleus flock. Genome-wide association studies were performed utilizing single-step Bayesian analysis. For wool traits, a total of 35 genomic windows surpassed the significance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…In our study, we discovered a relationship between the LEPR gene and such growth parameters as BW56, DCW, BrW, TW, and ADBWG. It should also be noted that a fairly large number of other studies have demonstrated the LEPR gene effects on growth, productivity, and reproduction in various farm animals [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ], including poultry [ 78 , 92 , 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we discovered a relationship between the LEPR gene and such growth parameters as BW56, DCW, BrW, TW, and ADBWG. It should also be noted that a fairly large number of other studies have demonstrated the LEPR gene effects on growth, productivity, and reproduction in various farm animals [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ], including poultry [ 78 , 92 , 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, the MED28 gene was found to be associated with body weight and intramuscular fat content [ 44 , 45 , 46 ]. In sheep, the MED28 gene was found to be associated with prenatal and postnatal body weights [ 47 , 48 ]. In pigs, the MED28 gene was found to be associated with muscle development [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MED28 gene is involved in milk production in ewes [43,52] and is also related to liveweight [54]. In addition, this gene has been linked to both pre and postnatal body weights in ewes [49,54].…”
Section: Discussionmentioning
confidence: 99%
“…The MED28 gene is involved in milk production in ewes [43,52] and is also related to liveweight [54]. In addition, this gene has been linked to both pre and postnatal body weights in ewes [49,54]. On the other hand, LAP3 also contributes to growth, milk production and feed efficiency traits in sheep [55].…”
Section: Discussionmentioning
confidence: 99%